-(5x-5)=

Simple and best practice solution for -(5x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-5)= equation:


Simplifying
-1(5x + -5) = 0

Reorder the terms:
-1(-5 + 5x) = 0
(-5 * -1 + 5x * -1) = 0
(5 + -5x) = 0

Solving
5 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -5x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -5x = 0 + -5
-5x = 0 + -5

Combine like terms: 0 + -5 = -5
-5x = -5

Divide each side by '-5'.
x = 1

Simplifying
x = 1

See similar equations:

| -113+5x+10x=97 | | 5-(h+3)=-1+2(h-3) | | 5-2x=x+9 | | 15-18=r | | X+9x-115=135 | | 87=-3(3x-8) | | 7x^2+5x= | | 7+5(1+4n)=6(5n-3) | | v=10t+3 | | -5x-172-8x=49 | | 3y+2x=49 | | 2m+5=4m-9 | | 10=6a-8-4a | | 5x-1=6x-3x+5 | | t=50w+25 | | 3v-7v=-16 | | 8x-(-2/3)x=16 | | -7x+9x-34=22 | | c=0.2 | | 4x+4=x+5 | | x+2x+1=4 | | -43-3x+7x=25 | | 17=1-3x-2 | | 2(n+5)=7n-16-4 | | 2+6x=7+3x | | 19-2(x+4)=3x-5+6x | | x^2+4x+3=4x^2+2x-1 | | 4x+2x+5x=130 | | 7x-12x-28=47 | | 3m-5+m=11 | | -6+1=25 | | -2=6-4p |

Equations solver categories